Stereoselective total synthesis of (+/-)-pleurospiroketals A and B - Thorat, Sagar S.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2021)
A full account of our efforts toward the stereoselective total synthesis of sesquiterpenoid-derived natural products (+/-)-pleurospiroketals A and B is described. Commercially available 3-methyl-2-cyclohexenone and 2,2-dimethyloxirane were used as key building blocks, and the substrate-controlled stereoselection was exploited to access the entire stereochemistry of these natural products. Initially, a planned synthetic route involving a [6,5]-bicyclic lactone intermediate was found to be insurmountable, and the later strategy comprising OsO4-NMO-mediated dihydroxylation of 3-methyl-2-cyclohexenone, followed by Luche reduction, Eschenmoser methylenation, and Bronsted acid-induced spiroketalization steps, was ultimately identified as the reliable strategy.

Solvent-driven mono- and bis-sulfenylation of (E)-beta-iodovinyl sulfones with thiols for flexible synthesis of 1,2-thiosulfonylalkenes and 1,2-dithioalkenes - Reddy, Raju Jannapu; Kumari, Arram Haritha; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2022)
The nature of solvent is a key factor for stereoselective mono-and bis-thiolation of (E)-beta-iodovinyl sulfones with thiols under basic conditions. A novel and unprecedented vicinal bisthiolation of (E)-beta-iodovinyl sulfones with thiols under the influence of K2CO3/DMSO at room temperature for quick assembly of (E)-1,2-dithio-1-alkenes is presented. Solvent-induced stereoselective monosulfenylation of (E)-beta-iodovinyl sulfones with thiols has also been established for the synthesis of both (E)- and (Z)-1,2-thiosulfonylethenes in MeCN and MeOH, respectively. Moreover, K2CO3-mediated desulfonylative-sulfenylation of (Z)-1,2-thiosulfonylethenes with thiols in DMSO furnished unsymmetrical (Z)-1,2-dithio-1-alkenes for the first time. The solvent-dependent versatile reactivity of (E)-beta-iodovinyl sulfones has been successfully explored to provide a set of (E)-/(Z)-1,2-dithio-1-alkenes and (E)-/(Z)-1,2-thiosulfonyl-1-alkenes in good to high yields with excellent stereoselectivities. Notably, this operationally simple process utilizes a broad substrate scope with good functional group tolerance and compatibility. The efficacy of the process has been proven for gram-scale reactions, and plausible mechanistic models are outlined on the basis of experimental results and control experiments.

Synthesis of N-functionalized 2,3-disubstituted benzofurans/naphthofurans from para-quinone methides and isocyanides via the [4+1] annulation pathway - Kale, Someshwar B.; Kumar, Manish; Shinde, Dinesh R.; Krishna, Gamidi Rama; Das, Utpal (Organic Chemistry Frontiers, 2023)
A scandium triflate catalyzed [4 + 1] cycloaddition reaction of 2-hydroxy-substituted para-quinone methides and isocyanides has been developed. This operationally simple, efficient and practical protocol provides straightforward access to a variety of N-functionalized 2,3-disubstituted benzofuran/naphthofuran derivatives with broad functional group compatibility and good scalability.